Implementasi Kurikulum Merdeka: Kendala dan Penanganannya dalam Pembelajaran di Sekolah - Ummi Nur Afinni Dwi Jayanti; Aulia Andin Kinanti; Ade Sekar Anggraini; Adyla Syukhraini Marwi; Putri Agustina Anggreni Arwira; Raini Dahriana Pulungan (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
The independent curriculum is a curriculum that has various learning topics and is more flexible for teachers and students. In fact, the government gives full authority and responsibility to all schools to create a curriculum that suits their needs and culture. The purpose of this research is to find and explain the obstacles faced by teachers in implementing the independent curriculum. Thus, research schools can determine the appropriate method to overcome this obstacle. This research uses descriptive qualitative method. The data collected is based on interviews and literature reviews from journals that discuss the independent curriculum. The results of the study show that teachers face a number of challenges in implementing an independent curriculum. Some of these challenges include the government not socializing the independent curriculum, preparing teachers to switch to an independent curriculum, and the availability of educational resources available to teachers, which are still focused on textbooks and handbooks.